Construction d'un outil d'évaluation de la qualité des actions d'accompagnement pédagogique. Synthèse d'échanges et d'analyse de pratiques professionnelles en Communauté française de Belgique - Didier Salmon; Dorothée Baillet; Marie Boulvain; Bernard Cobut; Michel Coupremanne; Dominique Duchâteau; Anne-France Lanotte; Pascale Dubois; Sabine Goemaere; Bernadette Noël; Mireille Houart; Pauline Slosse
The quality of student learning support services in higher education depends on several factors that need to be dealt with and analysed in order to enhance their effectiveness. A team of teachers and researchers from different Belgian higher education institutions, active in these fields, has explored the quality assurance process of these services in order to outline their main features, their difficulties and their limits.The members of the team confronted their experiences and elaborated a framework for assessment practices that was presented at the 25th AIPU congress held in May 2006 in Montpellier.This paper presents a framework that highlights the key questions that must be addressed in the assessment process of a student learning support unit. The dimensions of the framework are described and further clarified through three concrete examples.